Methanol Sensor-Less Control Strategy for Direct Methanol Fuel Cell Startup - Gan, Haibo; Sun, Hai (Frontiers in Energy Research, 2022)
It is critical and challenging to start direct methanol fuel cells (DMFC) from various environmental states to an ideal operating state by sensor-less method. This paper presents a novel methanol sensor-less startup control algorithm (SLSC) based on the unimodal relationship of current vs methanol concentration at a constant cell voltage during DMFC startup. A series of experiments indicate that the SLSC algorithm is capable to start a DMFC under various initial concentrations and initial temperatures, and can be easily adjusted to reduce the startup time or improve the energy efficiency. The wide applicability and easy adjustment characteristics give the SLSC algorithm a potential prospect in DMFC system.